PENGARUH INDEKS PENDIDIKAN, INDEKS KESEHATAN DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI SUMATERA BARAT TAHUN 2013-2019 - Dwi Putri Ramadhani; Menik Kurnia Siwi (Universitas Negeri Padang, 2022)
This study aims to determine the effect of the independent variables on the education index, health index and economic growth on the dependent variable of the human development index in West Sumatra Province in 2013-2019 either partially or simultaneously. This study uses quantitative methods and the type of data used is secondary data obtained from the Central Statistics Agency (BPS) of West Sumatra. The data using the Eviews 9 data processing tool. The results of this study indicate that (1) Partially (t test) the education index has a positive and significant effect on the human development index. Furthermore, the health index has a positive and significant effect on the human development index and economic growth has a positive effect on the human development index. (2) Simultaneously (Test F), the joint effect is that the education index, health index and economic growth have a significant effect on the district/city human development index in West Sumatra Province in 2013-2019. This research is expected to be a reference for the government to make decisions and evaluate policies in improving the quality of life of the residents of districts/cities in West Sumatra Province through the human development index.